Political Dynamics of Law and Siyasah Shar'iyyah in Egyptian Islamic Law Reforms: Transformation of Women's Rights Protection - T Muhammad Zamanhuri; Safaruddin Safaruddin; Safriadi Safriadi (Siyasah Wa Qanuniyah, 2025)
Family law reform in Egypt is an important response to social dynamics and the demands of modernity that require adjustments to Islamic legal regulations to be more contextual and responsive to the current conditions of society. This research uses a juridical-normative method with a literature review approach to analyse the historical development, reform process, and implementation of family law regulations in Egypt, especially those based on the principle of benefit (maslahah) in siyasah shar’iyyah. The results of the study show that Egypt has undergone various stages of family law reform, ranging from initial codification, amendments, to regulatory innovations that emphasise the protection of women’s and children’s rights, regulation of bride and groom’s consent, restrictions on polygamy, and the establishment of a minimum age of marriage. This reform succeeded in harmonising the principles of sharia with contemporary social demands through an adaptive and progressive model of siyasah shar’iyyah. In conclusion, family law reform in Egypt is not just a formal adjustment, but also a substantive transformation that strengthens legal certainty and social justice. This study makes a significant contribution to the study of Islamic law and family law reform in Muslim countries by offering a contextual and applicable model of siyasah shar’iyyah implementation.